Rusty Spider Wasp Tachypompilus ferrugineus - Sarah Elizabeth Anderson; Andrea Lucky (EDIS)
The rusty spider wasp, Tachypompilus ferrugineus, is a large, reddish orange wasp with conspicuous iridescent blue to violet wings. Aptly named, the rusty spider wasp specializes in hunting large spiders which it paralyzes and provides for its offspring to consume. These eye-catching wasps can be seen perusing loose soil for spider burrows, nectaring at flowers, or dragging large spiders back to their nests. https://edis.ifas.ufl.edu/in1247